Perancangan Sistem Informasi Akuntansi Menerapkan Metode Waterfall - Apelina Sitorus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In the business world, accounting knowledge plays a very important role in carrying out the company's operations. If accounting knowledge in the company is applied well, the company can be more professional and wise in making decisions so that the decisions taken really support the success of the business. In writing this final assignment the author tries to design an accounting information system application at CV. FLORENCE MOTOR. To make it easier to calculate cash receipts and disbursements from the computerized system, Ms. Word, Ms. Excel becomes easier by using the Visual Basic Studio Net 2008 application. So from there the author tries to provide a solution in the accounting information system application process on CV. FLORENCE MOTORS. Namely by designing the application using Microsoft Visual Basic 2008 and designing the database using MySQL and Cystral Report as a display of the results of the report, in this way the information system design meets the needs according to what is used. The results of this program can help in working on financial reports for the company CV. FLORENCE NOTOR well and quickly.